Electrical and interface properties of Au/DNA/n-Si organic-on-inorganic structures - Okur, Salih; Yakuphanoğlu, Fahrettin; Ozsoz, Mehmet; Kadayifcilar, Pinar Kara (Elsevier, 2009)
The effect of the thickness and coverage rate of a DNA film on the electrical and interface properties of Au/DNA/n-Si organic-on-inorganic structures has been investigated. The thin film properties of the DNA deposited on n-Si wafer were characterized by atomic force microscopy. The effect of the thickness and coverage rate of the DNA layer was investigated by evaluating electrical parameters, such as the barrier height, ideality factor, series resistance, and interface state density. The thickness and coverage rate of the DNA layer significantly affects the electrical properties of the Au/DNA/n-Si organic-on-inorganic structures. The interface state density properties of the Au/DNA/n-Si diodes were determined by conductance technique. The results show that the interface state density decreases with decrease in both film thickness and coverage rate of the DNA in an acetate buffer, modifying the electronic parameters of the Au/DNA/n-Si diodes. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Organic/inorganic junction; DNA; Ideality factor